Employee engagement moderates the influence of work-life balance and job satisfaction on the performance of civil servants in the Secretariat of Ende Regency - Aldi Saputra MZ Mochsen; Yupono Bagyo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The aim of this research is to examine and analyze the influence of work-life balance on ASN performance, job satisfaction on ASN performance, employee engagement on ASN work-life balance, employee engagement on ASN job satisfaction, employee engagement on ASN performance, employee engagement moderates the influence of work-life balance on ASN performance and employee engagement moderates the influence of job satisfaction on ASN performance. This research is explanatory research, the population in this research is ASN in the Secretariat Environment of Ende Regency, namely 113 employees with a total sample of 53 samples. The data analysis method used in this research is path analysis. The test results show that there is a significant influence between work-life balance on ASN performance, there is a significant influence between job satisfaction on ASN performance, employee engagement influences work-life balance. Employee engagement has a significant effect on job satisfaction, there is a significant influence between employee engagement and ASN performance. Employee engagement is proven to be a moderating variable on the influence of work-life balance and job satisfaction on ASN performance.